Learning to be a good orthographic reader - Castles, A; Nation, K (2008)
Recent years have brought about rapid advances in our understanding of reading and how it develops, particularly in relation to the importance of alphabetic coding skills. However, much less has been known about the transition from alphabetic decoding to the rapid and automatic orthographic recognition of words, which is the hallmark of skilled reading. The purpose of this special issue is to focus specifically on orthographic processes in reading and how they are acquired. The present paper provides an overview of the special issue, drawing attention to key themes that run through the various contributions. © United Kingdom Literacy Association 2008.